High-skilled immigration policy in Europe - Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2010)
Whether Europe will be able to stand up to its internal and external challenges crucially depends on its ability to manage its internal mobility and inflows of international migrants. Using a unique expert opinion survey, we document that Europe needs skilled migrants, and skill mismatch is to be expected. A review of current immigration policies shows that despite a number of positive recent developments Europe lacks a consistent strategy to address this challenge effectively, paralyzed by the notion of fortress Europe, which we argue should be abandoned. Since significant political tensions can be expected between native actors that favor and disfavor further immigration, improving European immigration policies and procedures is a formidable challenge. This task involves the need to improve Europe's image among potential migrants, especially the high-skilled ones.
Keywords: F22; J61; 330; high-skilled migration; mobility; immigration policy; Europe; European Union